Order-disorder structural transition in Pr3+-doped Ba3Ga2O6 for rewritable and write-once-read-many optical data storage. Issue 16 (15th August 2022) - Luo, Xiaobo; Liu, Ying; Long, Zhangwen; Hu, Songhan; Yang, Shuai; Zhou, Dacheng; Wang, Qi; Yang, Yong; Wen, Yugeng; Qiu, Jianbei
Abstract: The emerging challenges of the big data era, both in storage density and security, require the development of the next-generation optical data storage materials. Here, we report for the first time a photo-stimulated luminescence (PSL) material, Ba3 Ga2 O6 : Pr 3+, for rewritable optical storage and write-once-read-many data preservation. Ba3 Ga2 O6 : Pr 3+, with an isolated deep trap depth in the range 1.26–1.53eV, has been used for data encoding/decoding under the excitation of 254 nm UV light and by the simulation of an 808 nm NIR laser. Meanwhile, the phosphor allows for high-security write-once-read-many optical memory by taking advantage of the irreversible change of the photoluminescence (PL) color from blue to green (a binary blue '0' and green '1' code) irradiated by 365 nm UV light. The comprehensive investigations indicate that the irreversible PL switching is as a result of the order-disorder structural transition by thermal treatment. The new persistent luminescence material not only exhibits promising applications in sustainable rewritable data storage, but also paves the way for write-once-read-many optical information storage with a high level of security.